ULTRASTRUCTURE AND FUNCTIONAL MORPHOLOGY OF TEGUMENT IN MALE AND FEMALE TREMATODES DENDRITHOBILHARCIA PURVERULENTA (BRAUN, 1901) (TREMATODA: SCHISTOSOMATIDAE) - RIMMA MEYRAMOVNA UALIYEVA; KANAT KOMBAROVICH AKHMETOV (International Journal of Pharma and Bio Sciences, 2016)
The functional and morphological method based on the data of electron microscopy is a broad spectrum of facts that allow researchers to assess and compare the extent and the level of development of certain structures and their role in adaptation to the conditions in the localization organs. This article is devoted to studying epithelial tissues of the Dendrithobilharzia purverulenta dioecious trematodes by means of electron microscopy with involvement of histological techniques for the purpose of determining the overall morphology of helminths. Data has been obtained about the ultrastructure of the tegument layers and the muscular system in bions of both sexes.